Comanche society : before the reservation - Betty, Gerald, 1965- (Elma Dill Russell Spencer series in the West and Southwest, 2002)
"Once called the Lords of the Plains, the Comanches were long portrayed as loose bands of marauding raiders who capitalized on the Spanish introduction of horses to raise their people out of primitive poverty through bison hunting and fierce warfare. More recent studies of the Comanches have focused on adaptation and persistence in Comanche lifestyles and on Comanche political organization and language-based alliances. In Comanche Society: Before the Reservation, Gerald Betty develops an exciting and sophisticated perspective on the driving force of Comanche life: kinship. Betty details the kinship patterns that underlay all social organization and social behavior among the Comanches and uses the insights gained to explain the way Comanches lived and the way they interacted with the Europeans who recorded their encounters."--Jacket